Comparación de técnicas diagnósticas de tuberculosis porcina en dos establecimientos de cría confinada en Argentina - Magnano, G.G. (2010)
The diagnosis of tuberculosis in live animals is carried out using primarily by the tuberculin test (TT), however only few reports only show the results of this diagnostic test in swine. The objective of this study was to compare the TT with pathological and microbiological fi ndings in swine. A total of 307 sows were injected with avium PPD and bovine PPD following the standard technique. Tissues samples for bacteriological tests and histological exams were collected from 171 animals after slaughter. The following results were obtained: 14.4% (44) tested positive to avium PPD, 1.9% (6) to bovine PPD, 3.9% (12) to both PPD and 79.8% (245) were negatives. Only 4 samples were culture positives typifi ed by Mycobacterium bovis, M. avium, M. fl avescens y M. scrofulaceum. Neither macroscopic nor histological examinations revealed lesions compatible with TB.